A Triple Salting‐Out Effect is Required for the Formation of Ionic‐Liquid‐Based Aqueous Multiphase Systems. Issue 47 (19th October 2017) - Passos, Helena; Costa, Sara H.; Fernandes, Ana M.; Freire, Mara G.; Rogers, Robin D.; Coutinho, João A. P.
Abstract: Novel aqueous multiphase systems (MuPSs) formed by quaternary mixtures composed of cholinium‐based ionic liquids (ILs), polymers, inorganic salts, and water are reported herein. The influence of several ILs, polymers, and salts was studied, demonstrating that a triple salting‐out is a required phenomenon to prepare MuPSs. The respective phase diagrams and "tie‐surfaces" were determined, followed by the evaluation of the effect of temperature. Finally, the remarkable ability of IL‐based MuPSs to selectively separate mixtures of textile dyes is shown. Abstract : Three's a crowd : A simultaneous, triple salting‐out effect is required to form ionic‐liquid‐based three‐phase aqueous systems. These novel aqueous multiphase systems (MuPSs) were used for the selective separation of textile dyes, demonstrating their great potential in environmental and industrial applications.